Mesenchymal Stem Cell Application and Its Therapeutic Mechanisms in Intracerebral Hemorrhage - Yang, Guoqiang; Fan, Xuehui; Mazhar, Maryam; Yang, Sijin; Xu, Houping; Dechsupa, Nathupakorn; Wang, Li (Frontiers in Cellular Neuroscience, 2022)
Intracerebral hemorrhage (ICH) is one of the leading causes of death and long-term disability worldwide. The ICH is characterized by motor and sensory dysfunction that is usually associated with poor prognosis. However, there is no effective treatment available currently. In recent years, the neuroprotection and repairment capacity of mesenchymal stem cells (MSCs) has been widely investigated after ICH. MSCs therapy have demonstrated improved outcomes for treating ICH-induced neuronal defects. The neural network reconstruction and neurological function recovery were enhanced in rodent ICH models through the mechanisms of neurogenesis, angiogenesis, anti-inflammation, and anti-apoptosis. MSCs also exert many unique biological effects, including self-recovery by producing growth factors and cytokines, regenerative repair, immunomodulation, and neuroprotection against oxidative stress, providing a promising cellular therapeutic approach for the treatment of ICH. Taken together, our goal is to discuss the characteristics following ICH, including the mechanism and potential promising therapeutic targets of MSCs, aiming at providing new clues for future therapeutic strategies. Furthermore, some efficient strategies for the outcome improvement of MSCs transplantation were proposed.